Poster Media Program Promosi Kesehatan Pencegahan Dismenore dengan Pola Makan Anti Inflamasi Berbasis Penyembuhan Melalui Nutrisi (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2026)
Adolescent reproductive health is an important aspect that requires special attention, especially regarding the problem of dysmenorrhea or menstrual pain. Dysmenorrhea is often considered normal, even though it can reduce the quality of life and disrupt the learning activities of young women. One factor that influences dysmenorrhea is nutritional status and diet. This community service activity aims to increase the knowledge of young women about preventing dysmenorrhea through health promotion using posters with an anti-inflammatory diet approach based on "Healing Through Nutrition". The activity was carried out at the UPT SMA 9 Bulukumba on May 6, 2025, targeting 20 young women. The activity method included the planning, preparation, implementation, and evaluation stages, with a pre-test and post-test to assess the level of knowledge of participants. The results showed a significant increase in adolescent knowledge about preventing dysmenorrhea. Before the activity, 50% of respondents had poor knowledge, 40% had sufficient knowledge, and only 10% had good knowledge. After the intervention, 80% of respondents had good knowledge and 20% had sufficient knowledge, with no category of poor. These results indicate that poster media is effective in increasing adolescents' knowledge about dysmenorrhea and the importance of an anti-inflammatory diet as a non-pharmacological effort to prevent it.